Brazilian scientific production on pharmaceutical care from 1990 to 2009 - Funchal-Witzel, Maria Denise Ricetto (2011)
Brazilian scientific production on pharmaceutical care was identified based on articles indexed on the Medline, Embase, Lilacs, Web of Science and International Pharmaceutical Abstracts databases. Sixty-three articles published in both national and international journals were retrieved. With regard to authors, 72.3% were from the Southeast and South Regions, and 60.8% were affiliated to public universities. In relation to the type of studies, 85.7% were descriptive, and the most frequently researched fields were community pharmacies, hospitals and primary health care units. Articles were original in 65.1% of cases, updates in 20.6%, and reviews in 7.9%. An increase in publications commenced in 2006. In 31.7% of cases, authors had adopted a bibliographical study design, 28.6% qualitative study, 23.8% intervention, and 15.9% observational study design. The most researched subjects were elderly with chronic diseases. The importance of stimulating the conducting of experimental and qualitative studies, as well as amplifying authorship affiliated with the service area, foreign authors and with research in a wide variety of practice settings were highlighted. Despite the limited quantity of articles, an increase in their number as well as in their scope and quality is expected, so as to create further knowledge that contributes to the recognition of pharmacists' actions by patient healthcare teams.